2021
DOI: 10.1155/2021/6691305
|View full text |Cite
|
Sign up to set email alerts
|

mir-182-5p Regulates Cell Growth of Liver Cancer via Targeting RCAN1

Abstract: Regulator of calcineurin 1 (RCAN1) is an endogenous protein that is involved in the regulation of the occurrence and progression of a variety of cancers, but currently, people know little about its potential mechanism. This study investigated the function and mechanism of RCAN1 and miR-182-5p in liver cancer cells. In this study, reliable data demonstrated that RCAN1 suppressed cell proliferation, migration, invasion, and cell cycle progression of liver cancer. Additionally, the expression of RCAN1 was noted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…For those with liver cancer, miR-182-5p overexpression has been shown to have diagnostic and prognostic relevance ( 52 ). In concordance with our results, in liver cancer tissues and cell lines, miR-182-5p was recently found to be substantially expressed, according to a study ( 53 ). MiR-182-5p stimulated liver cancer cell proliferation by downregulating the regulator of calcineurin 1 (RCAN1).…”
Section: Discussionsupporting
confidence: 93%
“…For those with liver cancer, miR-182-5p overexpression has been shown to have diagnostic and prognostic relevance ( 52 ). In concordance with our results, in liver cancer tissues and cell lines, miR-182-5p was recently found to be substantially expressed, according to a study ( 53 ). MiR-182-5p stimulated liver cancer cell proliferation by downregulating the regulator of calcineurin 1 (RCAN1).…”
Section: Discussionsupporting
confidence: 93%
“…MiR-182-5p is a high-priority miRNA in HCC, and is closely associated with early recurrence and overall survival in patients ( 21 , 22 ). Numerous studies have shown that miR-182-5p is dramatically overexpressed in HCC and could enhance the ability of migration, invasion, adhesion and proliferation of HCC cells via repressing multiple targeting genes, such as FOXO3a ( 21 ), Hepatitis C virus p7 trans-regulated protein 3 (P7TP3) ( 23 ), and regulator of calcineurin 1 (RCAN1) ( 24 ). Furthermore, high-throughput sequencing has revealed that miR-182-5p expression is dramatically increased in fatty liver-related fibrosis ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies demonstrated that microRNAs (miRNAs) negatively regulate RNA targets at the post-transcriptional level (Cheng et al 2015 ). In HCC, oncogenic miRNAs, including miR-877, miR‐572, and miR-182-5p, negatively regulate RCAN1 to promote HCC progression (Zheng et al 2021 ; Song et al 2019 ; Shi et al 2018 ). Thus, RCAN1 expression was reduced in primary HCC compared to adjacent non-cancer liver tissues (Zheng et al 2021 ; Song et al 2019 ; Shi et al 2018 ).…”
Section: Rcan1 Expression Regulation and Function In Cancermentioning
confidence: 99%
“…In HCC, oncogenic miRNAs, including miR-877, miR‐572, and miR-182-5p, negatively regulate RCAN1 to promote HCC progression (Zheng et al 2021 ; Song et al 2019 ; Shi et al 2018 ). Thus, RCAN1 expression was reduced in primary HCC compared to adjacent non-cancer liver tissues (Zheng et al 2021 ; Song et al 2019 ; Shi et al 2018 ). The inhibitory effect of RCAN1 in HCC was further refined to its subtype RCAN1.4 (Jin et al 2017 ).…”
Section: Rcan1 Expression Regulation and Function In Cancermentioning
confidence: 99%
See 1 more Smart Citation